Gangguan Berbahasa Sekunder Anak Autis dalam Komunikasi Interpersonal dan Model Intervensi Penanganannya - Basri, Muh. Bahly; Ilham, Muhammad; Yasinta, Iin Nur (Fakultas Teknik Universitas Negeri Makassar, 2024)
This research was conducted to see the reactions of language disorders in children with autism and the intervention model for handling them. This type of research is a literature review (literature review). The data in this study are secondary data, including the speech of children with autism with secondary language disorders and the intervention model of the disorder. The data source is research articles. The data technique was carried out through literature studies. The results of this study were speech acts of children with autism were assertive, expressive, and directive speech acts. Assertive speech disorder occurs in the function of stating, notifying, and complaining. Expressive speech disorder occurs in the error function of the survivor and the blame. Directive speech disturbance occurs in the request and question function. The development of a model for handling secondary language disorders in children with autism is the Behavior System Card (BS Card) model. The BS Card model can improve language disorders in children with autism through developing receptive language and increasing awareness, increasing focus (eye contact), and increasing learning motivation.